Ultrasonographic findings in patients with shoulder pain - Khan, Md Shah Zaman; Rahman, Nayema; Ferdousi, Mahfuz Ara; Khatoon, Rabeya; Taher, Mohd Abu (BIRDEM Medical Journal, 2019)
Background: Shoulder pain is a common musculoskeletal condition and high frequency ultrasonography is an accurate non-invasive imaging technique for evaluating patients with painful shoulder. This study was designed to determine the ultrasonographic findings in patients with shoulder pain and to compare the clinical diagnosis established by physical examination to high frequency ultrasonographic findings. Methods: Thirty patients with shoulder pain were included in the study between the period from December 2017 to April 2018 in BIRDEM General Hospital, Dhaka, Bangladesh. All had a physical examination performed by a physician. Ultrasonographic examination was carried out within three days of the physical examination by two sinologists, who had no knowledge of the clinical findings. Results: Total patients were 30 with mean age 52.20±7.52 years and male female ratio 2:3. On examination out of these thirty patients, impingement syndrome was positive in 93.3% (Neer) and 76.7% (Hawkin), supraspinatus tendinitis in 83.3% (Jobe’s), biceps tendinitis in 30.0% (Yergason’s test) and 33.3% (Speed’s maneuver), subscapularis tendinitis in 3.3% (Gerbers lift off test) patients. Sonographic alteration was found in a total of 28 (93.33%) patients. Forty five pathologies were detected; 46.67% patients had single pathology, 40% had two and 6.67% had three pathologies. The structure most frequently involved was the supraspinatus tendon (35.50%). The long head of biceps tendon (17.78%) and the acromioclavicular joint (26.67%) were also frequently involved. Infraspinatus tendinopathy, subscapularis tendinopathy and subcaromial bursitis were present in small percentage. Significant difference was found between clinical examination and ultrasound findings. Conclusion: Ultrasonography may be a useful tool to improve diagnosis in painful shoulder. Birdem Med J 2019; 9(3): 218-222